STUDI POTENSI SENYAWA DERIVATIF FLAVONOID DARI TANAMAN GENUS MACARANGA TERHADAP PROTEIN E6 HPV DENGAN METODE DOCKING MOLECULAR - Veliyana Londong Allo; Djihan Ryn Pratiwi (JURNAL KIMIA MULAWARMAN, 2019)
Interaction study of active compounds of a medicinal plant with cervical cancer cells using the Docking Molecular (In Silico) method. In this research design the active compound sophoraflavanone B, 5,7,3 ', 4'-tetrahidroxy-3,6-diprenylflavone, apigenin and quercetin are first calculated using a quantum approach based on SCF method set 3-21G to obtain a stable compound form and has the lowest energy. Stable compounds interact with cervical cancer cells obtained from protein bank data (GDP) that have been prepared previously to obtain an inhibitory energy value, the number of hydrogen bonds and other factors that influence a Docking Molecular calculation. The interaction of compounds 5,7,3 ', 4'-tetrahydroxy-3,6-diprenylflavone against E6-HPV of 4 hydrogen bonds with a distance of 2.7-3.23 Å.